Factor influencing export of palm oil in Malaysia / Nur Aina Mohd Mohsein Dzakurnain - Mohd Mohsein Dzakurnain, Nur Aina (Faculty of Business and Management, 2016)
This paper investigates factors that influence export of palm oil in Malaysia using palm oil price, exchange rate and soybean oil price as independent variable for 35 years from the period 1980 to 2014. The relationship is examined by undertaking regression analysis using time series data from 1980 to 2014 that collected from International Financial Statistics. The purpose of the study is to see the relationship and effect among the selected variables whether the relationship is positive or negative by using Multiple Linear Regression, the model are tested by using E-Views software. From the result of Multiple Linear Regression, the study shows that exchange rate and soybean oil price has no significant effect towards export of palm oil in Malaysia. Meanwhile, price of palm oil has a significant relationship towards export of palm oil in Malaysia.